2013
DOI: 10.1039/c2cc36698c
|View full text |Cite
|
Sign up to set email alerts
|

Shape-persistent H-bonded macrocyclic aromatic pentamers

Abstract: The use of multiple-center intramolecular H-bonds for the efficient construction of macrocycles of varying structures and functions is among the newest and the most noteworthy additions to the toolbox for macrocycle synthesis. This strategy has allowed the creation of sizable interior cavities as small as 2.8 Å and as large as 15 Å in radius in these H-bonded macrocycles with a number of them expressing tailor-made functions. While concentrating on our recent contributions to this fast-growing field, we will f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(40 citation statements)
references
References 88 publications
(130 reference statements)
0
39
0
Order By: Relevance
“…Non‐covalent interactions are necessary to identify versatile supramolecular synthons and to take advantage of such connectors in the assembly of crystal networks 13. The rational design, synthesis and assembly of functional materials by supramolecular synthons is an area of widespread attention 47. The effective strategies of crystal engineering are based on a detailed understanding of the way non‐covalent interactions interact, compete and guide the assembly of discrete building blocks (such as ligand,8 anion9 and guest molecules10) into extended solid‐state architectures 1113.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐covalent interactions are necessary to identify versatile supramolecular synthons and to take advantage of such connectors in the assembly of crystal networks 13. The rational design, synthesis and assembly of functional materials by supramolecular synthons is an area of widespread attention 47. The effective strategies of crystal engineering are based on a detailed understanding of the way non‐covalent interactions interact, compete and guide the assembly of discrete building blocks (such as ligand,8 anion9 and guest molecules10) into extended solid‐state architectures 1113.…”
Section: Introductionmentioning
confidence: 99%
“…[52,53] Zeng and co-workers systematically studied the selfcoupling of several meta-substituted amino acids under different reaction conditions. [48] They found that pentagonal macrocycles, such as 36a and 36b, [54] were always formed favorably. The crystal structure of 36a revealed that it formed a perfectly planar conformation with fivefold symmetry.…”
Section: Promotion Of Covalent and Noncovalent Macrocyclizationmentioning
confidence: 98%
“…Thus, this family of compact backbones has been widely applied for the construction of macrocyclic systems. [47,48] In 2004, Gong and co-workers reported the one-step synthesis of macrocycles 35a-d in 69-82% yields from the corresponding diamine and diacyl chloride precursors. [49] When benzene-1,4-dicarboxylic acid precursors were introduced, the cavities of the macrocycles could be enlarged remarkably.…”
Section: Promotion Of Covalent and Noncovalent Macrocyclizationmentioning
confidence: 99%
“…As the central part of ah ydrogen bond, ap roton is responsible for the conformation of oligoamide foldamers [1][2][3][4] ando ligohydrazide macrocycles, [5][6][7] and it can directt he formation of macrocyclic oligoamides [8][9][10][11] and Schiff bases. As the central part of ah ydrogen bond, ap roton is responsible for the conformation of oligoamide foldamers [1][2][3][4] ando ligohydrazide macrocycles, [5][6][7] and it can directt he formation of macrocyclic oligoamides [8][9][10][11] and Schiff bases.…”
Section: Introductionmentioning
confidence: 99%